1989
DOI: 10.1007/bf01410349
|View full text |Cite
|
Sign up to set email alerts
|

Melt drawing as a route to high performance polyethylene

Abstract: Well established routes for obtaining stiff and strong polyethylene (PE) involve solid state drawing either of solution crystallized gel films or melt crystallized spherulitic PE. The aim of this work is to show the potential of melt deformation as an alternative route for obtaining highly oriented products. Our previous work on the melt deformation route showed that oriented PE fibers could be directly extruded under appropriately controlled conditions [8,9]. Here, we show that PE films (or filaments) can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 24 publications
10
33
0
2
Order By: Relevance
“…As per Bashir and Keller, 9 the longer chains crystallize earlier than the shorter chains during drawing from melt. Thus, a combination of chains having different length may have a dissolution effect where the shorter chains play a plasticizing role for longer chains, like solution-crystallization of PE with less entanglements.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…As per Bashir and Keller, 9 the longer chains crystallize earlier than the shorter chains during drawing from melt. Thus, a combination of chains having different length may have a dissolution effect where the shorter chains play a plasticizing role for longer chains, like solution-crystallization of PE with less entanglements.…”
Section: Introductionmentioning
confidence: 89%
“…Such advantages of HMW on ductility for drawing from PE melts have been examined by Kaito et al, 7,10 van Aerle et al, 8 and Bashir and Keller. 9 However, it has been also reported that much higher MW over 10 6 never gives the high ductility. 9,10 Thus, there may be an optimum MW for drawing from melt, as well as the solid-state drawing, depending on the drawing techniques, initial morphologies, and MW distribution (MWD).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[1][2][3][4][5] Transient crystallization into a hexagonal form occurs during oriented crystallization into a final orthorhombic form during melt-drawing of UHMW-PE, as determined by in situ wide-angle X-ray diffraction (WAXD) measurements using synchrotron radiation. [6] Furthermore, we examined the correlation between this transient crystallization and molecular entanglement characteristics of the sample films, i.e., MW or MW distribution (MWD).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] The temperature at which UHMWPE flows is 215°-220°C. 23,32 Complete fusion occurs at temperatures exceeding 220°C, the higher temperatures necessary for sufficient disentanglement and chain translation.…”
Section: Sem Morphology Of Fracture Surfacesmentioning
confidence: 99%